The Association of Contraceptive Use, Non-Use, and Failure with Child Health - Finlay, Jocelyn E (International Journal of Child Health and Nutrition, 2013)
Objective: To examine the association of contraceptive use in the interpregnancy interval with subsequent child health outcomes in low- and middle-income countries. Design: A cross-sectional analysis of nationally representative household samples was performed. A modified Poisson regression model was used to estimate unadjusted and adjusted relative risk ratios for high prevalence outcomes. Setting: Low- and middle-income countries. Population: Births to women aged 12-49 years for which this birth occurred 12-79 months prior to the interview were included. The sample for analysing infant mortality was comprised of 453,795 children from 35 low- and middle-income countries across 67 Demographic and Health Surveys conducted between 1990 and 2011. Main Outcome Measures: Infant mortality, stunting, underweight, wasting, diarrhoea, and anaemia. Results: Contraceptive use in the interpregnancy interval, even if contraceptive failure resulted in birth, had a positive effect on all child health outcomes compared to non-use of contraception in the interpregnancy interval. The positive effect of contraceptive use was the lengthening of the interpregnancy interval, but it also had a direct positive effect on child health, independent of birth interval. Conclusions: Extending the interval between births had a positive effect on child health outcomes, and contraceptive use had a positive effect on child health independent of the birth spacing effect. Additionally, contraceptive failure did not adversely affect child health outcomes.